Charmon ramagei sp. nov., a new Charmontinae (Hymenoptera: Braconidae) from Reunion, with a synopsis of world species - Rousse, Pascal (Zootaxa, 2013)
Charmon ramagei sp. nov. is described from Reunion. The small subfamily Charmontinae now comprises nine extant and one fossil species. This new species is readily distinguishable from other Charmon spp. due to the presence of a Y-shaped mid-longitudinal propodeal carina. The key to the world species of the subfamily is updated, and a synoptic table provided to compare their critical morphological features.